An investigation of the experience of students who progress from further education to higher education nursing degree programmes - Brown Clarke, Eunice (Trinity College Dublin. School of Education. Discipline of Education, 2025)
This study explores the experience of further education graduates who have accessed places on nursing degree programmes in higher education. For this study semi structured interviews were conducted with thirty six further education graduates who are now undergraduate students in nursing degree programmes in higher education. The participants were graduates from twenty two further education providers in the Republic of Ireland who had achieved the QQI level 5 Nursing Studies or Healthcare Support Award. Participants were attending eleven higher education institutions in the Republic of Ireland and studying four different disciplines of nursing. Using a thematic analysis of the data generated five themes emerged: `Personal growth, `Insight to nursing, `FE pedagogy, `Preparation for HE and `Relationships in HE. The findings of this study indicated that the experience of further education increased participants self-confidence, built resilience and reinforced their commitment to pursuing a nursing degree. They also perceived that they were well prepared for the transition to higher education having developed study, academic and independent learning skills. Knowledge gained in PLC modules along with competency in clinical skills encompassed in the QQI level 5 awards contributed to reduced stress levels for the participants, particularly in the first year of undergraduate studies. The work experience component of further education provided an insight into nursing as a profession and encouraged the development of a dual identity of learner and nurse. This facilitated academic and social integration by participants on the undergraduate programme and fostered a sense of belonging in the communities of the academic environment and the clinical placements. The influence of further education continued in the progression through the undergraduate years. In conclusion this study makes recommendations for practice, policy and further research in further and higher education to enhance the experience of students in tertiary education.
APPROVED
Keywords: Further education; Access to higher education; Nurse education; Transition to higher education; Identity and belonging.